The role of organizational culture in the implementation of lean tools towards operational performance in an aerospace company - Md Lazi, Farah Nadhirah (2023)
The global marketplace has undergone a significant transition that characterizes industry in the twenty-first century. Delivering high-quality products quickly drives manufacturers to optimize their operations, manufacturing processes, and all potential supply chain nodes. This is due to intense global competition, quick technological change, advances in manufacturing and information technology, and discerning customers. To obtain a competitive edge, the pursuit of this optimization has increased the need for faster product creation, more flexible production, waste reduction, better process control, effective workforce use, and worldwide reach. The purpose of this research is to investigate the role of organizational culture in the implementation of lean tools toward operational performance in an aerospace company. The study is based on a survey conducted and data collected from an aerospace company located in Melaka. 346 targeted respondents from the aerospace company ranging from the executive to non-executive levelsfamiliar with lean wereinvolved in this study. Then, structural equation modeling is used to test all the hypotheses.The findings of the data analysis indicate that lean tools implementation has a positive relationship with operational performance. The second finding, lean tools implementation, has a positive relationship with organizational culture, but the third finding states that organizational culture does not have a relationship with lean tools and operational performance. Researchers find the implementation of that lean tool can maximize cost reduction in any organizational culture setting but requires a supportive organizational culture to maximize quality, delivery, and flexibility improvements. Future research is necessary for a more diverse context to confirm the generalization of the results. Future research may be extended to investigate the effects of lean tools implementation and organizational cultural aspects on measures of financial, social, and environmental performance. There is a scarcity of research on the cultural aspects of organizations related to lean tool implementation. This research is an attempt to fill that gap. The results obtained would help managers to understand better the linkage between lean tools implementation and operational performance, considering the aspect of cultural change management in an organization. The outcome of this research provides useful indications of how organizations can work to sustain the philosophy of lean within their workplace. This study could expand the boundary of the existing literature and contributes to the body of knowledge related to the effect of lean tool implementation theoretically and methodologically.